Diversity and morphology of marine planktonic species of the diatom family Thalassionemataceae from the Mexican Pacific - Hernández-Becerril, David U.; Esparza-Álvarez, María Auxilio; Pérez-Mendoza, L. Aleli; Becerril-Bobadilla, Francisco J.u.; Pérez-García, Roberto (Phytotaxa, 2025)
Based on the analysis of net-phytoplankton and bottle samples obtained during different oceanographic cruises (period 1986–2019) along coasts of the Mexican Pacific, we studied the diversity, morphology and distribution of species of the diatom family Thalassionemataceae. Diatoms of this family are marine and planktonic forms, with a characteristic “needle shape” and extremely long cells, which may form chains (colonies) and may be abundant in polar, subpolar, and in tropical and subtropical waters. Twelve taxa (11 species and one variety) belonging to three genera of the Thalassionemataceae were studied by light-, scanning-, and transmission electron microscopy (LM, SEM and TEM), including seven Thalassionema taxa (6 species and one variety), two Thalassiothrix species and three Lioloma species. Additionally, two unidentified morphotypes were found and studied by SEM; they are related to known species but differ in some characters and current observations are insufficient to propose new taxa. Morphological details of critical characters are described for each species, such as valve symmetry (iso- or heteropolarity), different ends (head-pole and foot-pole), structure of the marginal areolae, presence of marginal spines and bubble-like structures, apical protrusions or spines and labiate processes; in some species the formation of chains and the chloroplasts cell content were documented, as well as the structure of cingular bands. Additionally, the particular morphological character of the double lipped structures forming the internal labiate structure of the apical rimoportulae was detected in three Thalassionema identified species and one Thalassionema unidentified species. A contemporary account of the family is provided here, and four new records are annotated, including Thalassionema kuroshioensis, a recently described species, and the warm-water forms Thalassionema synedriforme, Thalassiothrix gibberula and Thalassiothrix spathulata. We found that Thalassionema frauenfeldii, T. kuroshioensis, T. nitzschioides (and its variety parvum) and T. pseudonitzschioides, Lioloma delicatulum, L. elongatum and L. pacificum were widespread along the Mexican Pacific, whereas Thalassionema bacillare, T. synedriforme, and Thalassiothrix gibberula and T. spathulata were more restricted to tropical and subtropical areas.